BIOMECHANICAL PRINCIPLES PHYSICAL REHABILITATION OF CHILDREN WITH CEREBRAL PALSY - S. D. Korshunov; K. V. Davletyarova; L. V. Kapilevich (Бюллетень сибирской медицины)
Aim. We studied the basic biomechanical principles of physical rehabilitation of children with cerebral palsy.Materials and methods. Methods of Motion Tracking and electromyography investigated the biomechanical characteristics of gait in children with cerebral palsy. It is shown that the main differences between dynamic stereotype walk pediatric patients is to delay moving forward center of gravity and the disorganization of the lower limb movements (especially knee) in the vertical plane. Prevailing flexion - leading position of the lower extremities during locomotion cycle associated with limitation of motion in the hip joint, offset by an increase swinging body, weakening activity in the rear shock phase and its sharp increase in the fourth phase. Changes in the structure of the movement of the shoulder girdle and upper extremities can be considered as compensatory. Characteristically excessive involvement in the locomotion of the calf muscles and the rectus muscles of the back, with the central mechanisms gipersinhronizatsii activity of motor units are the primary mechanism for adaptation in a group of children that are capable of self-locomotion.Results. As a result of the research it shows that in motor rehabilitation of children with cerebral palsy should include the following elements: exercise to maintain the body balance when performing arm movements, exercises for coordination of hand movements, including motor brushes, exercises to increase mobility in the hip joints and in the back, exercises designed to exercise the calf muscles, the front thigh muscles and the rectus muscles of the back, massage to relieve hyper calf muscles.